MAKING A MATCH GAMES TO IMPROVE STUDENTS’ VOCABULARY - Lina, Desi (Publikasi dan UKI Press UKI Toraja., 2022)
The objectives of the research were to examine whether the use of Match Games Improve the students’ vocabulary and to find out the strengths and the weaknesses of Match Games. The researcher was applied pre-experimental design the population is the seven grade students of SMPN 1 Hulu Sungkai in academic year 2021/2022. The total number of populations is 240 students. The researcher was used total sampling technique. relatively baseline knowledge based on their test examination average scores. The total number of samples was 30 students from class VII. In analyzing the numerical data, the writer was used SPSS for windows. After implementing the research, the researcher concludes that the use of Matching Games in teaching English vocabulary enriches the students’ vocabulary; it is proved by the mean score of the students’ posttest. The t-test of the students’ vocabulary achievement in posttest was smaller than ? (0.000 < 0.05). It meant that the H1 of the hypothesis was accepted